Source Characteristics of the 28 September 2025 Mw 5.5 Kutahya-Simav Earthquake Sequence in Western Turkiye - Altuntaş, Nurdeniz; Taymaz, Tuncay (Copernicus GmbH, 2026)
The Anatolian Plate has a complex tectonic structure. This is mainly caused by the northward movement of the Arabian Plate and subduction along the Hellenic Arc. Many large earthquakes in Türkiye occur along the right-lateral North Anatolian Fault and the left-lateral East Anatolian Fault. Western Anatolia is dominated by north-south extension. This extension formed the Aegean Extensional Province, which includes E-W trending grabens and NW-SE oriented active faults. One of the key structures in this area is the Simav Fault Zone (SFZ). In this study, we focused on the 28 September 2025 Kütahya-Simav (Mw 5.5) earthquake located on the SFZ. Earthquake catalogs provide basic source information. However, they are often not enough to fully describe fault geometry and fault segmentation. For this reason, a detailed source analysis is needed. In this study, we present a moment tensor solution for the 2025 Kütahya-Simav earthquake. The analysis is carried out using the ISOLA and regional waveform inversion. Broadband seismic data from the AFAD and KOERI networks are used. Both point-source and possible multiple-source inversions are performed. These inversions are used to estimate the focal mechanism, seismic moment, and centroid depth. The quality of the solutions is evaluated using Variance Reduction (VR) and Condition Number (CN) values. The results are compared with previous studies and historical data from the Simav Fault Zone. This allows us to obtain a more reliable solution than standard catalog results. The findings explain the present stress pattern and fault behavior in the Kütahya-Simav region.